EFFECT OF STOCK MARKET CONCENTRATION ON THE GROWTH OF CORPORATE BOND MARKET IN KENYA - Wanyama, Dr. David W. (International Journal of Finance, 2017)
Purpose: The purpose of this study was to analyze how stock market concentration influences the growth of corporate bond market in Kenya. Methodology: The study used descriptive and causal research designs. Secondary data was used. The sample of the study consisted of daily and monthly time series covering six years beginning January 2009 to December 2014. Unit root tests using Augmented Dickey-Fuller (ADF) and Phillips-Perron tests were done. The study used Eviews econometric software to facilitate empirical analysis of data. Results: Regression of coefficients results shows that stock market concentration and corporate bonds are positively and significant related (r=0.014, p=0.017). Unique Contribution to Theory, Practice and Policy: The study recommends that concerted efforts should be made to improve market concentration in the corporate bonds market so that it can operate optimally. The existing concentration affected the stock and corporate bond markets positively. However, policy makers should be careful not to allow a higher stock market concentration as this will adversely affect the financial markets (El-Wassal, 2013).